2014
DOI: 10.1186/1748-717x-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and toxicity of proton beam therapy for advanced cholangiocarcinoma

Abstract: BackgroundWe examined the efficacy and toxicity of proton beam therapy (PBT) for treating advanced cholangiocarcinoma.MethodsThe clinical data and outcomes of 28 cholangiocarcinoma patients treated with PBT between January 2009 and August 2011 were retrospectively examined. The Kaplan–Meier method was used to estimate overall survival (OS), progression-free survival (PFS), and local control (LC) rates, and the log-rank test to analyze the effects of different clinical and treatment variables on survival. Acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 16 publications
0
49
0
1
Order By: Relevance
“…More recently, proton beam therapy (PBT) has been utilized in the treatment of unresectable and recurrent iCCA in small studies in an effort to deliver more effective, tumor‐specific doses of radiation . PBT has been used to treat cholangiocarcinoma in a group which contained a small number of iCCA patients (n = 6) . In this study, overall survival at 1 year was 49%, which is comparable to other radiation therapies.…”
Section: Methodsmentioning
confidence: 66%
“…More recently, proton beam therapy (PBT) has been utilized in the treatment of unresectable and recurrent iCCA in small studies in an effort to deliver more effective, tumor‐specific doses of radiation . PBT has been used to treat cholangiocarcinoma in a group which contained a small number of iCCA patients (n = 6) . In this study, overall survival at 1 year was 49%, which is comparable to other radiation therapies.…”
Section: Methodsmentioning
confidence: 66%
“…Less OAR dose can translate to safer dose-escalation in various tumors, which has already been tested for other cancers (71). Aforementioned studies have also demonstrated improved LC with higher BED values (39). Additionally, as the treatment of GI tumors often requires concurrent or sequential multimodality therapy with surgery and/or chemotherapy, PBT may be an ideal RT modality for treating GI malignancies, as it may more safely allow for multimodality therapy (72).…”
Section: Discussionmentioning
confidence: 99%
“…Makita and colleagues examined 28 patients, 10 of which were locally or regionally recurrent (39). Of the 18 primary tumors, 6 each were intrahepatic and hilar, 3 distal extrahepatic, and 3 gallbladder.…”
Section: Biliary System and Gallbladdermentioning
confidence: 99%
“…Like SBRT, this results in significantly reduced doses to surrounding tissues [84]. A retrospective analysis in 28 patients with new or recurrent inoperable cholangiocarcinoma undergoing PBT reported 1-year PFS and OS of 29.5 and 49%, respectively [85]. However, toxicities were common; 29 grade I, 16 grade II and eight grade III toxicities were reported.…”
Section: Radiation Oncological Therapiesmentioning
confidence: 99%